Self-image goals, compassionate goals and innovative work behavior: The role of organizational support for innovation across countries - Montani, F.; Torres, T.; Ferreira, M. C.; Mendonça, H.; Junça Silva, A.; Courcy, F.; Dagenais-Desmarais, V. (Journal of Business Research, 2021)
The present study examines the relationship between interpersonal goals – i.e., self-image and compassionate goals – and innovative work behavior by taking into account the organizational context and the country as boundary conditions. By integrating self-presentation theory with cross-cultural research on innovation, we hypothesized that in high innovation-supportive organizations, employees from more collectivistic, higher power distance and higher uncertainty avoidance countries (Brazil) would be more engaged in innovative behaviors when they hold self-image goals, whereas those from more individualistic, lower power distance and lower uncertainty avoidance countries (Canada) would be more innovative when they are driven by compassionate goals. The results from moderated regression analyses on two independent samples – i.e., 291 Brazilian employees and 114 Canadian employees from different organizations – supported our predictions. We conclude that the organizational context and the country play a key, synergistic role in shaping costs and benefits of interpersonal goals for employee innovativeness.